The high temperature pigments based on CeO2 - Šulcová, Petra; Trojan, Miroslav (Univerzita Pardubice, 2000)
The synthesis of new inorganic pigments is investigated in our laboratory. The main attention is directed to the preparation of high-temperature colour pigments which can be used for colouring of ceramic glazes. The synthesis of these pigments is based on high-temperature calcination of starring oxides. The optimum conditions for the syntheses of pigments have been estimated. The pigments and ability tu dye ceramic glazes.
Keywords: anorganická technologie; anorganické pigmenty; syntézy; vysokotepelné materiály; keramika